Understanding the word "analysis" in the context of requirements engineering - Prado Leite, Julio César Sampaio do (2005)
I have been teaching, in reality, preaching, the importance of a clear understanding for the word “analysis”. It is my conclusion, after years of exposure to the term “system analysis”, that it has mislead lots of young people how wishes to understand the process of software construction, in special the initial steps of the process. My main point is that you can only analyze something that you know. However, educators in the areas of information systems and software engineering always focused the “system analysis” as a modeling discipline, where specifications were written and formalization was sought at the very early stages of conceptions of a system. Based on this bias on modeling, analysis was a way of enforcing syntax rules of a given modeling language, which provide ways of applying verification protocols. As such, not enough emphasis was directed to the goal of really understanding the concepts involved and the needs of the clients. (Párrafo extraído del texto a modo de resumen)